1986
DOI: 10.1002/1097-0142(19860715)58:2<219::aid-cncr2820580203>3.0.co;2-a
|View full text |Cite
|
Sign up to set email alerts
|

Immunologic alterations in xeroderma pigmentosum patients

Abstract: Nine xeroderma pigmentosum (XP) patients were investigated. In comparison to a normal control group the XP patients had a reduced OKT-4 lymphocyte subpopulation, reduced response of lymphocytes to phytohemagglutinin in autologous serum, and diminished delayed hypersensitivity skin reaction. The possible contribution of ultraviolet irradiation to the observed immunologic alterations, and the link of these alterations to the susceptibility of patients for malignant transformation is discussed. Cancer 58:219-221,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0
2

Year Published

1988
1988
2014
2014

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(25 citation statements)
references
References 16 publications
(3 reference statements)
1
22
0
2
Order By: Relevance
“…In addition to the DNA repair defects found in all XP patients, there have been a variety ofcellular immune abnormalities noted in isolated XP patients: decreased delayed-type hypersensitivity reactions (impaired responses to intradermal recall antigens and decreased dinitrochlorobenzene sensitization), decreased T-cell proliferative responses to mitogens, decreased CD4/CD8 ratio, and one report each of severe combined immunodeficiency and systemic lupus erythematosus ( 15,(18)(19)(20)(21)(22)(23)(24)(25). Norris et al (26,27) reported decreased NK cell activity in five patients with XP, when compared to normal controls, and in patients with trichothiodystrophy or Cockayne syndrome.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the DNA repair defects found in all XP patients, there have been a variety ofcellular immune abnormalities noted in isolated XP patients: decreased delayed-type hypersensitivity reactions (impaired responses to intradermal recall antigens and decreased dinitrochlorobenzene sensitization), decreased T-cell proliferative responses to mitogens, decreased CD4/CD8 ratio, and one report each of severe combined immunodeficiency and systemic lupus erythematosus ( 15,(18)(19)(20)(21)(22)(23)(24)(25). Norris et al (26,27) reported decreased NK cell activity in five patients with XP, when compared to normal controls, and in patients with trichothiodystrophy or Cockayne syndrome.…”
Section: Introductionmentioning
confidence: 99%
“…Although CHS was induced in non-irradiated XPA mice as well as wild-type mice, UVB-induced local and systemic immunosuppressions were greatly enhanced in XPA mice (Miyauchi-Hashimoto et al, 1996). There are some studies that patients with XP have defects in cell-mediated immunity such as impaired cutaneous responses to recall antigens and a contact sensitizer (Morison et al, 1985;Wysenbeek et al, 1986;Goldstein et al, 1990). Our studies using XPA mice suggested that the immunologic dysfunction in XP patients is not innate but acquired possibly after exposures to the sunlight.…”
mentioning
confidence: 99%
“…We are aware of only one report ofa child who had agammaglobulinemia and abnormal T cell response to PHA (7). Although the etiology of the immunologie alterations in XP is unknown, it is hypothesized there is a relationship between UV irradiation and immunologic changes, and that these changes may also play a role in the development of UV-induced skin tumors (5).…”
Section: Discussionmentioning
confidence: 99%